2022
DOI: 10.1158/1535-7163.mct-21-0234
|View full text |Cite
|
Sign up to set email alerts
|

Microneedle-mediated Intratumoral Delivery of Anti-CTLA-4 Promotes cDC1-dependent Eradication of Oral Squamous Cell Carcinoma with Limited irAEs

Abstract: Head and neck squamous cell carcinoma (HNSCC) ranks sixth in cancer incidence worldwide and has a 5-year survival rate of only 63%. Immunotherapies—principally immune checkpoint inhibitors (ICI), such as anti-PD-1 and anti-CTLA-4 antibodies that restore endogenous antitumor T-cell immunity—offer the greatest promise for HNSCC treatment. Anti-PD-1 has been recently approved for first-line treatment of recurrent and metastatic HNSCC; however, less than 20% of patients show clinical benefit and durable responses.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…With systemic administration, the immune system may be over-stimulated and dosing can result in autoimmunity and subsequent autoimmune disease. Indeed, in studies involving microneedle delivery of anti-CTLA-4 in an orthotopic mouse model of head and neck cancer, Gutkind and coworkers ( Gilardi et al, 2022 ) showed anti-tumor responses at doses significantly lower than that needed using systemic administration. Additionally, the lower lymphatic dose reduced the lymphocyte infiltration of normal tissues that characterizes the immune related adverse events (irAEs) often suffered by cancer patients.…”
Section: Directing Pharmacological Delivery To the Lymphaticsmentioning
confidence: 99%
“…With systemic administration, the immune system may be over-stimulated and dosing can result in autoimmunity and subsequent autoimmune disease. Indeed, in studies involving microneedle delivery of anti-CTLA-4 in an orthotopic mouse model of head and neck cancer, Gutkind and coworkers ( Gilardi et al, 2022 ) showed anti-tumor responses at doses significantly lower than that needed using systemic administration. Additionally, the lower lymphatic dose reduced the lymphocyte infiltration of normal tissues that characterizes the immune related adverse events (irAEs) often suffered by cancer patients.…”
Section: Directing Pharmacological Delivery To the Lymphaticsmentioning
confidence: 99%
“…MN-assisted delivery of DNA vaccines [ 89 , 128 , 129 ], tumor cell lysates [ 130 , 131 ], immune adjuvants required for immunotherapy, or immune checkpoint inhibitors [ 71 , 132 ] has also been developed for the treatment of superficial tumors. Subunit vaccines are an ideal choice for immunotherapy due to their good biosafety.…”
Section: Mn-mediated Treatment and Diagnosis Of Superficial Tumorsmentioning
confidence: 99%
“…Using a mouse model of HNSCC, Gilardi M team developed a novel, local delivery strategy based upon an array of soluble microneedles (MN). Local-MN delivery of anti-CTLA-4 in vivo can protect animals from irAEs observed, but this process relies on CD8 T cells and conventional dendritic cell type 1 (cDC1) (64). Additionally, the 3D culture models of the tumorpromoting microenvironment in vitro will contribute to a comprehensive understanding of the mechanisms of malignant metastasis in vivo and facilitate the development of novel anti-tumour drugs (65,66).…”
Section: Immunotherapeutic Efficacy and Immune-related Adverse Eventsmentioning
confidence: 99%